(3GdJYdjbGJ (B((3aj GdMceI (B) (3Yf GdTjN GdaGQGHi hGdTjN GHf SjfGs - (3HgefjGQ Hf GdeQRHGf GdGPQHjLGf, CHh GdMSf,J (B458 (3g` s
(3ChdgG (B:s
(3ai Ydi GdHGQi hebOeI GdcdGe ai eYfi EVGaI GdYGde Edi GdeYdhe s
(3HChdg agQS ai (B" 20" (3hQbI Yedg CHh GdYHGS GdaVd Hf eMeO GdchcQi S`(B503(3`Is
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B77s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B7 - (3U (B204 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGK (B(3204) s
Keywords: (3GdadSaI hGdefWbs